The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17541/optimum.684605
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Gelecekleriyle İlgili Kaygı ve Beklentilerinin Belirlenmesi

Abstract: Dünyada yaşanan önemli değişimlerin meydana getirdiği belirsizlikler başta genç nüfus olmak üzere çoğu insanın geleceğe yönelik kaygı ve beklenti düzeylerini etkileyebilmektedir. Bu bağlamda araştırmada Türkiye'de turizm eğitimi alan öğrencilerin kaygı ve beklenti düzeylerinin belirlenmesi ve kaygı ve beklenti düzeylerini etkileyen faktörlerin ortaya konması amaçlanmaktadır. Araştırmada nicel araştırma yöntemlerinden yararlanılmış ve veri toplama aracı olarak anket tekniği kullanmıştır. Türkiye'de kamu ve vakı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
5
0
7
Order By: Relevance
“…Therefore, it has been observed that since the first day of the pandemic, people have increased anxiety, fear, anxiety, insecurity and uncertainty due to both the increase in the number of deaths and serious patients and the negative media reports (Lai et al, 2020). Especially the younger generation has been adversely affected by this process (Zengin & Şengel, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, it has been observed that since the first day of the pandemic, people have increased anxiety, fear, anxiety, insecurity and uncertainty due to both the increase in the number of deaths and serious patients and the negative media reports (Lai et al, 2020). Especially the younger generation has been adversely affected by this process (Zengin & Şengel, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Situations such as the restriction of a large part of the society, the uncertainty regarding the development of the COVID-19 pandemic, and the disruption of educational activities have adversely affected the psychological state of university students who are isolated at home (Ellis, Dumas, & Forbes, 2020;Ye et al, 2020;Vindegaard & Benros, 2020). COVID-19 process affected the social life, daily life, and mental state of university students, especially the younger generation (Bueno et al, 2021;Zengin & Şengel, 2020). With this study, it is thought that it is important to determine the relationship between rumination and COVID-19 anxiety, which is thought to increase among university students with the pandemic, and it will contribute to the studies to be done in this direction.…”
Section: Introductionmentioning
confidence: 93%
“…Üniversite öğrencilerinin sınıf düzeyleri ilerledikçe ekonomik beklentilerle ilgili gelecek kaygılarının da arttığı (Gizir vd., 2010); gelecek beklentisinin azaldığı ve dördüncü sınıf öğrencilerinde en düşük düzeyde olduğu görülmektedir (Şimşek, 2010). Zengin ve Şengel (2020) üniversite öğrencilerinin sınıf düzeyleri ilerledikçe kaygılarının da arttığını ancak gelecek beklentilerinin azaldığını belirtmektedir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…Bu araştırmada 23 yaş ve üzeri yaş düzeyindeki öğrencilerin diğer yaşlardaki (22,21,20) öğrencilerden görüşlerinin düşük olması, son dönemde yaşadıkları sosyal ve ekonomik sorunlarla ilişkilendirilebilir. Üniversite öğrencilerinin yaşları ilerledikçe beklentileri azalmaktadır (Zengin ve Şengel, 2020). Buna karşın alanyazında yaşı büyük yükseköğretim öğrencilerinin diğer öğrencilerden stresle baş etme, problem çözme ve değerlendirmede uyguladıkları farklı yöntem ve stratejilerle başarılı oldukları ve gelecek umutlarının daha yüksek olduğu görülmektedir (Williams ve Mc Gillicuddy, 2000).…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified